Sodium Imbalance and Mortality Rate in Septic Patients - Otniel, W; Dian, A (KnE Life Sciences, 2019)
Sepsis is a life-threatening organ dysfunction caused by an irregular host response to infection. There are cytokines that regulate various inflammatory responses. Dysregulation of cytokines causes endothelial dysfunction, vasodilation and increased capillary permeability, then causes cellular leakage syndrome that interferes with regulation and intravascular hypovolemia, cellular dysfunction, and ultimately tissue death. As the main extracellular cation, sodium (Na) is the most osmotically active solute in the human body. Sodium is usually a parameter that is ignored, but it has a predictive value. This study aimed to evaluate the prognostic value of serum Na in adult patients with a diagnosis of sepsis.A total of 406 patients were diagnosed with sepsis during 2017 at Dr. Moewardi hospital. Data collection was performed in a retrospective cohort during the period of January-December 2017. Data distribution was evaluated by using Kolmogorov-Smirnov test, followed by Kruskal-Wallis analysis for comparison between groups and by using chi-square test. We determined the relative risk (RR) to assess the risk of death. We found that in patients with hypernatremia RR= 7.25 (95% CI 0.91-57.58; p = 0.03), in mild hyponatremia RR= 0.45 (95% CI 0.22 - 0.91; p= 0.02), both were comparable to healthy control. In conclusion, there is no significant difference in the risk of death between patients with hypernatremia group and normonatremia, serum sodium levels are not the main parameters that indicate the risk of death but can be used as a supporting parameter of risk of death in septic patients.